Let's talk 2 - Jones, Leon (Cambridge University Press, 2008)
The popular speaking and listening text Let's Talk has been thoroughly revised. A lower level (Let's Talk 1) and an upper level (Let's Talk 3) have been added to provide a complete three-level series. Let's Talk is designed to develop oral communication skills. The series includes a variety of interesting and innovative topics that encourage students to express their feelings, ideas, and opinions. Interaction comes naturally as students complete clear-cut tasks in pairs or groups. Frequent language support throughout the text facilitates fluency. Let's Talk 1 is for students at the high-beginning/low-intermediate level. Students discuss a variety of topics such as hobbies, personality, money and shopping, food, health, foreign customs, and the future. The Student's Book contains 16 four-page thematic units divided into two-page lessons. Review units after every four units recycle key vocabulary. Communication activities at the back of the text provided additional speaking practice.